Study guides

Q: Simplify x plus 2

Write your answer...

Submit

Related questions

x(x + 2)

11+(7-3)2=

Assuming simplify = factor...x3 - 3x + 2 = (x-1)(x2+x-2)

3x^2 + x + 2x^2 = 5x^2 + x

3x

(x+2)/(x+2) = 1x equals infinity

Factor it out: (x+2) squared

No

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

-x - 2 + 15x = 14x - 2 = 2(7x - 1)

x + 5 + 4 = x + 9

This would simplify as 4x-5

-7 + 2(x-3) = -7+2x-6 = 2x - 13

6

-3x2 + 16x + 12 = -3x2 + 18x - 2x + 12 = -3x*(x - 6) - 2(x - 6) = -(3x + 2)*(x - 6)

The answer is 5x+3y. (5 xs and 3 ys)

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer

- - x + 3 = x + 3

-9

Combine all lie term: x + x - 22x = -20x 2 + 1 = 3 So the answer is -20x +3 or 3 - 20x

x2 + 4x = x(x+4)

x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)

Factor the numerator. x+1 is one of its factors (otherwise, it wouldn't be possible to simplify it). Then cancel the identical factors in the numerator and the denominator.

x + 61.4 cannot be simplified.